2021
DOI: 10.3390/sym13060931
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Empirical Mode Decomposition with Adaptive Noise with Convolution Based Gated Recurrent Neural Network: A New Deep Learning Model for South Asian High Intensity Forecasting

Abstract: The intensity variation of the South Asian high (SAH) plays an important role in the formation and extinction of many kinds of mesoscale systems, including tropical cyclones, southwest vortices in the Asian summer monsoon (ASM) region, and the precipitation in the whole Asia Europe region, and the SAH has a vortex symmetrical structure; its dynamic field also has the symmetry form. Not enough previous studies focus on the variation of SAH daily intensity. The purpose of this study is to establish a day-to-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…With the renewal and iteration of the neural networks, many spatiotemporal prediction models are constantly proposed and applied to the prediction of various systems in the atmosphere [76][77][78][79][80][81][82][83]. The ensemble DL model is one of the most typical cases.…”
Section: Related Work and Research Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…With the renewal and iteration of the neural networks, many spatiotemporal prediction models are constantly proposed and applied to the prediction of various systems in the atmosphere [76][77][78][79][80][81][82][83]. The ensemble DL model is one of the most typical cases.…”
Section: Related Work and Research Gapmentioning
confidence: 99%
“…Previous studies also have shown that adding mathematical processing methods to the machine learning model will improve the stability and fitting effect of the model to a certain extent. For example, Peng et al [79] investigated that the CEEMDAN + ConvGRU method can accurately predict the intensity of the South Asian high (SAH) and achieved better stability than the traditional machine learning method. The ensemble empirical mode decomposition (EEMD) combined with CNN + LSTM method proposed by [90] also can predict the El Niño index more accurately and stably.…”
Section: Related Work and Research Gapmentioning
confidence: 99%